Hospitalization for transurethral bladder resection reduces quality of life in Danish patients with non-muscle-invasive bladder tumour. (3rd May 2016) - Mogensen, Karin; Christensen, Karl B.; Vrang, Marie-Louise; Hermann, Gregers G.
Abstract: Objective The aim of the study was to evaluate the impact of transurethral resection of bladder tumour (TURBT) on patients' quality of life (QoL) and to validate a tool to quantify problems associated with TURBT in a Danish population.Materials and methods A prospective study was carried out using a combination of questionnaires and interviews. The study included 165 consecutive patients undergoing a TURBT owing to non-muscle-invasive bladder cancer (NMIBC) from 1 May 2011 to 30 April 2012. Seven patients were selected for interviews. The Danish translation of the QLQ-NMIBC24 Quality of Life Questionnaire for NMIBC, from the European Organisation for Research and Treatment of Cancer (EORTC), was used. The interviews were semi-structured. The reliability of the subscales quantifying QoL as defined by the EORTC was tested by computing Cronbach's coefficient alpha and confirmatory factor analysis. The interviews were analysed using the phenomenological method.Results The questionnaire was returned by 121 (77%) patients at a mean of 12 days after hospital discharge. Over half had substantial voiding problems and one-third had emotional concerns. These results were confirmed by the interviews. The mean ± SD score for urinary symptoms was 45.21 ± 23.9 and the mean score for the future worries subscale was 39.9 ± 29.9. Cronbach's coefficient alpha was 0.84 for the urinary symptom subscale and 0.93 for the future worries subscale, which satisfied the reliability criterion for clinical use.Conclusions This first prospective study on QoL following TURBT in patients with NMIBC shows that TURBT has a significant impact on QoL. The Danish version of the EORTC questionnaire QLQ-NMIBC24 has been validated and confirmed in a Danish population.